Software to determine optimal oligonucleotide sequences based on hybridization simulation data - Hyndman, D (BioTechniques, 1996)
In the design of oligonucleotide sequences for targeting DNA or RNA sequences, it can be difficult to identify sequences that will hybridize only to the intended target. The term "sequence-specific" or "sequence-nonspecific" is often used to describe the interactions of an oligonucleotide with a mixture of DNA or RNA. Our new computer program, HYBsimulator (formerly OligoProbe DesignStation), creates a set of candidate oligonucleotides from a target gene. For each of the candidate oligonucleotides, a large sequence database is searched for sequences that will hybridize to the oligonucleotide. This is referred to as computer hybridization simulation (CHS). Using the nearest-neighbor model, the HYBsimulator takes into account mismatches in hybridization and calculates the melting temperature (Tm) or free energy for hybridization to all sequences in a database. The specificity of each oligonucleotide is then quantified by the number of genes that may hybridize and the predicted Tms or free energies of hybridization to those genes. The CHS data are used to select oligonucleotides based on their specificity with respect to a database